Tornwaldt Cyst: A Case Report Of Unusual Dental Symptoms - Mohd Rasoul, Asfizahrasby; Ibrahim, Norliwati (IIUM Medical Journal Malaysia, 2017)
Introduction: Tornwaldt's (Thornwaldt's) or nasopharyngeal cyst is an uncommon developmental benign cyst located in the midline postero-superior wall of nasopharynx. Incidence reported in general population is 0.06%. It occurred in the potential space due to outpouching of ectoderm into the pharyngobasilar fascia at the site where notochord attached to pharyngeal ectoderm. The cyst developed when the epithelial lining of the pouch secrets mucous following recurrent infection or trauma of the nasopharynx. Although majority of the cases are asymptomatic, patients may present with clinically-significant nasal, ear or cervical symptoms. Thus, most of Tornwaldt cyst cases were reported under otorhinolaryngology (ORL)-associated journals. However, patient presented with dental symptoms has never been reported before. This case is the first one as such to be reported.